Study of maternal and foetal outcome in post-term pregnancies - Shankar, Priya; KR, Hemalatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Post-term pregnancies are associated with significant foetal morbidity and increase in interventions which jeopardise the health of the fetus as well as the mother. The objective of this study was to determine the incidence, risk factors, maternal and foetal outcomes of such pregnancies. Methods: A retrospective study of 117 post-term pregnancies was studied over a period of one year, January to December 2016. Age, parity, amniotic fluid index, color of liquor, mode of delivery, maternal and foetal outcomes were studied in detail and analysed. Results: There were 10390 deliveries during our study period. 130 among them were post-term, 117 were included in the study, amounting to an incidence of 1.12%. Post-term pregnancy was noted to be higher in women of age group 21-25years (68.5%) and among primigravidae (51.2%). 66 women experienced vaginal delivery (56.4%) and 49 women underwent caesarean delivery (41.8%). Most common indications for caesarean section were foetal distress, oligohydramnios, and foetal growth restriction. NICU admissions were 16 babies and 2 early neonatal deaths were noted. Conclusions: Post-term pregnancy requires early detection, proper planning of pregnancy termination. These women should be offered induction of labour prior to 42 weeks of gestation age to avoid adverse maternal and perinatal outcomes.